Community Assistance Of Communities Affected By Covid-19 In Economic Recovery Through Entrepreneurship Program (Recycling Used Plastic Glass) In Jebung Kidul Village, Kec. Tlogosari Kab. Bondowoso: Pendampingan Komunitas Masyarakat Terdampak Covid-19 Dalam Pemulihan Perekonomian Melalui Program Wirausaha - Waziroh, Iro; Hosaini; Safitri, Muharafah Nur; Muzayyanah; Abrari, Achmad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bondowoso, 2022)
Community Community Assistance, namely Community University Partnerships from universities which is carried out directly by Lecturers in various forms. In this case, Community facilitators provide assistance using the ABCD method (Asset based community development) is a paradigm in community service, the principle of this approach leads to the context of understanding and internalizing assets, potential, strengths, and their utilization independently and maximally. which was carried out in the village of Jebung Kidul, Kec. Tlogosari kab. Bondowoso. With several forms, namely individual assets, discovery, dream, design, destiny, the first steps we take in this assistance are; (1) Create Initial Plan (2) Form Core Group (3) Sharing Method and Steps of ABCD Partnership to Core Group (4) Strategy for Making Asset Map (5) How to link between assets (6) How to choose Priorities, Low hanging fruits (7) How to prepare an action plan (8) Create an action plan (9) How to monitor and evaluate (10) How to make a report (11) Follow up plan. Community University partnership activities carried out in the village of Jebung Kidul, district. Tlogosari kab. Bondowso begins by looking at the condition of the community who has the potential to find assets in themselves and related community groups to hone and develop these assets by utilizing used plastic glass materials which are managed into a TAS to help the economy of the community who are being affected by the Covid-19 PSBB. This Community Service runs well and is able to realize a useful item so that the community is not only a housewife but has other useful activities.